2019
DOI: 10.3389/fneur.2019.00776
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lesion Location With Long-Term Recovery in Post-stroke Aphasia and Language Deficits

Abstract: Background: Recovery from post-stroke aphasia is important for performing the activities of daily life, returning to work, and quality of life. We investigated the association between specific brain lesions and the long-term outcome of four dimensions of aphasia: fluency, comprehension, naming, and repetition 12 months after onset in patients with stroke. Methods: Our retrospective cross-sectional observational study investigated the relationship between the Korean version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…developed a model which considers the overlap of lesions with known core language areas to predict individual patient performance on a battery of 21 aphasia measures (mean R 2 = 0.48, n = 70) 18 . This and earlier work suggest that a profile of aphasia impairments and severity can be inferred from lesion location and extent at the patient-level 19 , 20 . However there remains considerable unexplained variance in patient outcomes, and prognostic model performance may benefit from inclusion of additional functional variables 21 , 22 .…”
Section: Introductionsupporting
confidence: 64%
“…developed a model which considers the overlap of lesions with known core language areas to predict individual patient performance on a battery of 21 aphasia measures (mean R 2 = 0.48, n = 70) 18 . This and earlier work suggest that a profile of aphasia impairments and severity can be inferred from lesion location and extent at the patient-level 19 , 20 . However there remains considerable unexplained variance in patient outcomes, and prognostic model performance may benefit from inclusion of additional functional variables 21 , 22 .…”
Section: Introductionsupporting
confidence: 64%
“…For more accurate analyses, the origin of each image (coordinates: 0 × 0 × 0 mm 3 ) was reoriented such that it was located close to the anterior commissure. To analyze the lesion maps, segmentation and normalization were employed [8,11,24]. We used the MR segment-normalize and MR normalize functions of a plugin (available online: https://www.nitrc.org/projects/clinicaltbx/) for mapping in stereotaxic space using the normalization algorithm provided by SPM8 software (available online: http://www.fil.ion.ucl.ac.uk/spm/software/spm8).…”
Section: Lesion Analysismentioning
confidence: 99%
“…The exact role of Wernicke's area, including the role of the supramarginal gyrus in aphasia, is still controversial. Some studies have shown that it is closely related to aphasia and comprehension disorder 61,62 ; however, it has also been proposed that it only plays the role of phonetic representation rather than language comprehension 63 . If future studies use rs‐fMRI in SD queues to explore this area further, our results suggest that focusing on Wavelet‐ALFF in slow‐2 and slow‐3 bands may be useful.…”
Section: Discussionmentioning
confidence: 79%